Intellectual and Developmental Disabilities Research Centers: A Multidisciplinary Approach to Understand the Pathogenesis of Methyl-CpG Binding Protein 2-related Disorders. (1st October 2020) - Fagiolini, Michela; Patrizi, Annarita; LeBlanc, Jocelyn; Jin, Lee-Way; Maezawa, Izumi; Sinnett, Sarah; Gray, Steven J.; Molholm, Sophie; Foxe, John J.; Johnston, Michael V.; Naidu, Sakkubai; Blue, Mary; et al.
Highlights: RTT is a dynamic disorder involving stagnation and regression of brain development in early postnatal life. Studies should be designed as longitudinal to analyze trajectories rather than taking snapshots in time. New biomarkers and outcome measures that can be directly translated from animal models to patients have been identified. Synergistic and multidisciplinary efforts are needed to decode and treat the pathogenesis of the complex MeCP2 disorders. Abstract: Disruptions in the gene encoding methyl-CpG binding protein 2 (MECP2) underlie complex neurodevelopmental disorders including Rett Syndrome (RTT), MECP2 duplication disorder, intellectual disabilities, and autism. Significant progress has been made on the molecular and cellular basis of MECP2 -related disorders providing a new framework for understanding how altered epigenetic landscape can derail the formation and refinement of neuronal circuits in early postnatal life and proper neurological function. This review will summarize selected major findings from the past years and particularly highlight the integrated and multidisciplinary work done at eight NIH-funded Intellectual and Developmental Disabilities Research Centers (IDDRC) across the US. Finally, we will outline a path forward with identification of reliable biomarkers and outcome measures, longitudinal preclinical and clinical studies, reproducibility of results across centers as a synergistic effort to decode and treat the pathogenesis of the complex MeCP2 disorders.